The role of auditing in detecting tax evasion - Vržina, Stefan Ž. (International Journal of Economic Practice and Policy, 2017)
Forthcoming paper opens questions about new audit conducting area and new empirical challenge for audit profession – detecting tax frauds. A growing problem of tax evasion, expressed as an act of illegal reduction of tax liabilities, points out the inability of state authorities to reduce or neutralize tax evasion volume. Created as a consequence of previous fact, forthcoming paper has an objective to examine whether, and in which way, financial statements audit could contribute to inicial signalizing of tax evasion through expressing opinion about truth and objectivity of accounting statements. Special focus is put on related-party transactions with entities registered in offshore zones, which progressively become materially significant, thus becoming a subject of audit examination.
Keywords: tax evasion; financial statement; audit; audit opinion; offshore zones; materiality